Effect of vitamin E supplementation on oxidative stress in non-transfusion-dependent thalassemia - Ngarmpattarangkoon, Duangkamon; Pongtanakul, Bunchoo; Chanvorachote, Pithi; Meksawan, Kulwara (Progress in Nutrition, 2016)
Summary. Excessive free radical production is found in thalassemic patients, and this can lead to many complications. The objective of this study was to determine the effect of vitamin E supplementation on oxidative stress in the young patients with non-transfusion-dependent thalassemia (NTDT). Seventeen patients aged between 5-20 years participated in this study. They were divided into vitamin E group (supplemented with 10 IU/kg/day of vitamin E) and control group (no vitamin E supplementation). The levels of serum vitamin E and plasma malondialdehyde (MDA), hemolysis and complete blood count (CBC) were evaluated at baseline and at the end of the study (week 12). The results showed that after 12 weeks of the study, the subjects in the vitamin E group had significantly increased serum vitamin E levels (p < 0.01) and significantly decreased plasma MDA levels (p < 0.05) as compared to baseline, and these levels significantly differed from those in the control group (p < 0.05). In vitamin E group, the percentage of hemolysis induced by 2, 2’-azobis-2-methyl-propanimidamide dihydrochloride (AAPH) was significantly decreased as compared to baseline (p < 0.05) after vitamin E supplementation. There was no change in hemoglobin and hematocrit throughout the study. The results indicated that vitamin E supplementation in NTDT may benefit these patients in alleviating complications from oxidative stress.